Endothelial barrier dysfunction in septic shock. (March 2015) - Opal, S. M.; van der Poll, T.
Abstract The endothelium provides an essential and selective membrane barrier that regulates the movement of water, solutes, gases, macromolecules and the cellular elements of the blood from the tissue compartment in health and disease. Its structure and continuous function is essential for life for all vertebrate organisms. Recent evidence indicates that the endothelial surface does not have a passive role in systemic inflammatory states such as septic shock. In fact, endothelial cells are in dynamic equilibrium with a myriad of inflammatory mediators and elements of the innate immune and coagulation systems to orchestrate the host response in sepsis. The barrier function of the endothelial surface is almost uniformly impaired in septic shock, and it is likely that this contributes to adverse outcomes. In this review, we will highlight recent advances in the understanding of the signalling events that regulate endothelial function and molecular events that induce endothelial dysfunction in sepsis. Endothelial barrier repair strategies as a treatment for sepsis include modulation of C5a, high‐mobility group box 1 and VEGF receptor 2; stimulation of angiopoietin‐1, sphingosine 1 phosphate receptor 1 and Slit; and a number of other innovative approaches.